Analysis Effect of Product Quality, Price Perception, And Customer Loyalty to Samsung Mobile Phone Purchase Decisions on Sinar Mas Cell in Semarang City - Rizkiana, Citra; Suryawardana, Edy; GraciaFernandy, Maria Augustine (Economics and Business Solutions Journal, 2023)
The tighter the competition between similar products, companies compete with each other for consumers. The purpose of this study was to find out whether Product Quality, Price Perception, Customer Loyalty to Samsung Mobile Purchase Decisions on Sinar Mas Mobile in Semarang City.The population in this study was all customers or consumers who used or made mobile phone purchase decisions at sinar mas cells that found 185 customers. The purpose of sampling is the selection of samples based on the specific characteristics of 100 respondents. Data analysis methods use multiple linear regressions, coefficients of determination and hypothesis tests.The results of this study showed that with a product quality regression co-effectiveness meaning the quality of the product had a positive and significant effect on purchasing decisions. Variable the price perception has a positive and significant effect on the purchasing decision. Wheres variable customer loyalty has a positive and significant effect on purchasing decisions. Product Quality, Price Perception and Customer Loyalty together both positively and significantly affect purchasing decisions, this is evidenced in the F test.Based on the results of research that the decision to purchase Samsung phones on Sinar Mas phones in Semarang City in the medium category, and it is advisable to improve the Quality of Products offered, so that consumers against samsung phone brands in the cell space in Semarang City.